The Continental Divide: Anti-TNF Use in Pediatric IBD Is Different in North America Compared to Other Parts of the World - Peter C. Church; Jeffrey Hyams; Frank Ruemmele; Lissy de Ridder; Dan Turner; Anne M. Griffiths (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Use of anti-TNF therapies varies internationally. As an initiative of the international Pediatric IBD Network (PIBDNet), we compared global pediatric IBD anti-TNF practice patterns. Methods. Physicians were surveyed about anti-TNF use in Crohn’s disease (CD) and ulcerative colitis (UC). Chi-squared, independent samples Mann–Whitney U, or related samples Wilcoxon signed rank tests were used to compare groups. Results. 344 physicians treating pediatric IBD responded from 43 countries (54% North America, 29% Europe, 6% Oceania, 6% Asia, 3% Africa, and 2% South America). Respondents treated a median 40 IBD patients. CD was more commonly treated with anti-TNF than UC (40% vs. 10%, p<0.001). North Americans more often used anti-TNF (median 50% vs. 30%, p<0.001) and before immunomodulator (80% vs. 35% CD, p<0.001; 76% vs. 43% steroid-dependent UC, p<0.001). Anti-TNF monotherapy was more common in North America. Anti-TNF in combination with methotrexate, instead of thiopurine, characterized North American practices. North Americans more often continued immunomodulator indefinitely and less often adhered to standard infliximab induction dosing. Access limitations were more common outside North America and Europe for both CD (67% vs. 31%, p<0.001) and UC (62% vs. 33%, p<0.001). Conclusions. Anti-TNF use in North America varies significantly from elsewhere.